Local Government in Punjab: Comparative Analysis of PLGA, 2013 and PLGA, 2019 - Khan, Marryam (Journal of Pakistan Administration, 2021)
Devolution of political, administrative and financial powers to local level is essential for inclusive, need-based and equitable governance. The Constitution of Pakistan provides for a federal form of government, wherein authority is distributed between the federation and provinces. Article 140-A of the 1973 Constitution of the Islamic Republic of Pakistan states that the provinces shall “devolve political, administrative and financial” powers to local governments.2 In Pakistan, the legal history of decentralization includes the promulgation of Basic Democracies Ordinance, 1959 by President General Ayub Khan, Local Government Ordinance (LGO), 1979 by President General Zia-ul-Haq and LGO, 2001 by President General Pervez Musharraf. These laws are viewed as tools for earning political legitimacy and weakening of political forces.3 Notwithstanding this criticism, LGO, 2001 is seen as the most democratic local government framework introduced till date.4 Interestingly, LGO, 2001 was promulgated by a military ruler but abrogated by a democratic government in 2008.5 Thereupon, Punjab Local Government Act (PLGA), 2013 was introduced in the backdrop of the 18th Amendment and Article 140-A.6 However, elections under PLGA, 2013 were only held on directions of the Supreme Court of Pakistan (SCP). In 2019, the local governments were dissolved by the government upon passage of the PLGA, 2019.